Effect of Chloramphenicol on Rabbit Doe Fertility and Prenatal Development - Ngoula, Ferdinand; Borice, Tsafack; Herman, Ngoumtsop Victor; Bertin, Vemo Narcisse; Joseph, Tchoumboue; D’Alex, Tadondjou Tchingo (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
Chloramphenicol (CP) is a synthetic antibiotic with large spectrum, mostly used in human and veterinary medicine to fight against diverse infections. In the present study the effects of this antibiotic on some does reproductive parameters were evaluated on 24 nulliparous, sexually mature female (6 months). The animals were divided into 4 groups of 6 does each, comparable in terms of body weight. To each group was randomly attributed by gavage 25, 50 and 75mg of CP/kg of body weight 30 days before mating (6 females for 1 male) and during the whole gestation period. After sacrifice of the does on the 28th day post-coitum, the organs (ovaries, liver, and kidneys) and fetus were collected and were examined to detect eventual anomalies. The main results showed a non-significant increase (P>0.05) of the relative weight of the liver and kidneys and a non-significant decrease (P>0.05) of that of the ovaries with increase in the dose of CP. No abortions were registered no matter the dose of CP. Gestation index, the rate of fetal mortality and of fetal viability were not significantly affected by the dose of CP used. A decreasing (P<0.05) dependent dose of the average litter size, the average litter weight, the placenta and the gravid uterus, the number of placenta and the implantation sites were registered. However, a non-significant reduction (P>0.05) of the average weight of the fetus and their body measurement, the number of corpus luteum and the sex-ratio (M/F) were registered from treated animals in relation to the control animals. A dose-dependent increase (P<0.05) of number of pre and post-implantation resorptions were noted. The only anomaly registered was the insufficient fusion of the cranial bones at the dose 50 and 75mg/kg of CP. A significant decrease (P<0.05) of the level of proteins in the serum and ovaries were noted in animals treated in relation to those of the control group. It was concluded that CP administered at doses of 25, 50 and 75 mg/kg bw to pre and post-coital rabbit does, negatively affects fertility but has no significant teratogenic effects. Its use should therefore be limited or prohibited in husbandry.